The PREPARE Study: Acceptability and Feasibility of a Telehealth Trimodal Prehabilitation Program for Women with Endometrial Neoplasia - Elise P. Legault; Paula A. B. Ribeiro; Danielle Moreau-Amaru; Emmanuelle Robert; Sara Forte; Alain S. Comtois; Vanessa Samouëlian; François Tournoux (Current Oncology)
Patients with endometrial neoplasia (EN) often have multiple comorbidities and a higher surgical risk. Prehabilitation programs (PPs) combine various interventions to improve preoperative conditions and reduce impairment due to surgical stress. We conducted a pragmatic pilot study to evaluate the acceptability and feasibility of a trimodal telehealth PP (exercise, nutrition, and psychological support) for EN patients. The participants could select their exercise group: (1) a supervised PP (SPP), group sessions 3×/week; (2) a semi-supervised PP (SSPP), group session 1×/week, training alone 2×/week; or (3) a physical activity counseling session (PACS). Out of the 150 EN patients awaiting surgery screened during the 18 months of the study recruitment, 66% (99/150) were eligible, and 40% consented to participate (SPP, n = 13; SSPP, n = 17; PACS, n = 9). The overall dropout was low (13%; 5/39), with no significant differences across groups. No serious adverse events occurred. We observed a positive impact on different outcomes across the different groups, such as in the Functional Assessment of Cancer Therapy quality of life score (SPP; delta = 6.1 [CI: 0.9; 12.6]) and functional capacity measured using the 30″ sit-to-stand test (PACS delta = 2.4 [CI: 1.2; 3.6]). The same-day hospital leave was high in the SSPP group (54.5%). Our pilot telehealth PP seems to be safe, feasible, and well accepted and may procure clinical and patient-centered gains that need to be confirmed in a larger trial.